Strategi Manajemen Digitalisasi Pembelajaran PAI di Era Revolusi 4.0 di Tingkat SMP - Fitriani; Nadya Nur Ramdhani; Muhammad Irfan Athaillah; Fiqra Muhamad Nazib (Yayasan Al-Afif, 2024)
This study investigates the challenges and strategies of implementing digitalization in Islamic Religious Education (PAI) learning in Junior High Schools (SMP) in the era of the Industrial Revolution 4.0. Using the systematic literature review (SLR) method, the study identified key challenges, including the digital divide, limited digital literacy among teachers and students, and inadequate infrastructure. Effective strategies involve comprehensive digital literacy training for teachers, integration of digital platforms into the curriculum, and collaboration with external partners to increase resource availability. While digitalization promotes increased learning motivation, accessibility and innovative teaching methods, it also carries risks such as reduced focus, character education gaps and the digital divide. The findings emphasize the need for systematic planning and targeted programs to address these challenges and maximize the benefits of digitalization in PAI learning. This study highlights the importance of adaptive strategies to bridge the gap and optimize digital learning outcomes.